Controlling shareholdings, intellectual capital and firm performance: evidence from Malaysian listed firms - Jawad, Asif (2022)
This thesis examines how controlling shareholdings affect the efficiency of IC investments. Additionally, despite that IC is beneficial for firms, there is need to identify critical levels of IC investments. To identify this gap, this thesis examines the nonlinear relationship between IC investments and firm performance. At last, controlling shareholders as strong governance players have the ability to moderate the relationship between IC investments and firm performance. To connect these under researched areas of controlling shareholdings, IC investments and firm performance, this thesis retrieves data from Main Board of Bursa Malaysia for the period of ten years from 2009—2018 for 733 Malaysian public listed firms. This thesis utilize panel data regression approach to analyse the hypothesized relationships. This thesis also provide robustness using two-stage least square and alternative proxies of variables. The major findings reveals that controlling shareholdings have a non-linear (inverse U-shaped) relationship with efficiency of IC investments. That is, controlling shareholders having low (high) level of ownership increase (decrease) the efficiency of IC investments. Additionally, findings suggests that IC investments have non-linear (inverse U-shaped) relationship with firm performance. That is, excessive investments in IC investments are harmful rather than beneficial. At last, findings indicate that controlling shareholders moderate (positive or negative) the relationship between IC investments and firm performance. These findings indicate that controlling shareholders affect in two competing theoretical predictions of alignment effects and entrenchment effects. This thesis recommends that Malaysia for the sake of higher capital values should focus on managing the efficiency of IC investments. The findings of this thesis are fruitful for policy makers, managers (IC managers and HC managers) and future researchers.